2000
DOI: 10.1159/000025756
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast Involvement in Glycosaminoglycan Synthesis and Lipid Retention during Coronary Repair

Abstract: Myofibroblasts of adventitial origin have been linked to neointimal formation and remodeling after coronary injury. Accordingly, the goal of this study was to examine whether myofibroblasts contribute to focal accumulation of glycosaminoglycans (GAGs) and lipids during coronary repair. GAG synthesis was assessed by ex vivo labeling of balloon-injured porcine coronary arteries with 14C-glucosamine. The synthesis of total GAGs transiently increased at 8 days in the normolipemic model (a 2.2-fold incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…VFF are believed to transform into myofibroblasts in response to LP injury, and higher myofibroblast levels have been linked with increased collagen deposition [51]. Studies of lung and arterial tissue indicate that cell elastin [52] and GAG secretion [53] are also elevated with increasing myofibroblast phenotype. Furthermore, elevated VFF proliferation rates (fraction of cells expressing PCNA) were observed with increasing mesh size and decreasing modulus.…”
Section: Discussionmentioning
confidence: 99%
“…VFF are believed to transform into myofibroblasts in response to LP injury, and higher myofibroblast levels have been linked with increased collagen deposition [51]. Studies of lung and arterial tissue indicate that cell elastin [52] and GAG secretion [53] are also elevated with increasing myofibroblast phenotype. Furthermore, elevated VFF proliferation rates (fraction of cells expressing PCNA) were observed with increasing mesh size and decreasing modulus.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 On the other hand, histologic assessment of tissue from a black hole showed predominance of hypocellular matrix with areas of proteoglycans. [12][13][14][15] The predominance of proteoglycans could be related to general vascular wound-healing delay, 16 which can occur as late as 2 year following SES implantation. 17 In the present case, restenosis occurred from 3 to 16 months after SES implantation.…”
Section: Discussionmentioning
confidence: 99%
“…33 Our previous studies have shown that vascular tissues rich in proliferating fibroblasts produced higher amounts of sulfated GAG and exhibited avid lipid retention compared with differentiated SMCs. 34 Thus, oxidative stress and the synthesis of matrix proteins, which retain LDL, may promote oxidative lipid modifications and create conditions promoting early onset of SVG atherogenesis. This study has important clinical implications, providing biological rationale for the use of arterial conduits for coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%